Oral and Stool Microbiome Coalescence and Its Association With Antibiotic Exposure in Acute Leukemia Patients - Franklin, Samantha; Aitken, Samuel L.; Shi, Yushi; Sahasrabhojane, Pranoti V.; Robinson, Sarah; Peterson, Christine B.; Daver, Naval; Ajami, Nadim A.; Kontoyiannis, Dimitrios P.; Shelburne, Samuel A.; Galloway-Peña, Jessica (Frontiers in Cellular and Infection Microbiology, 2022)
Failure to maintain segregation of oral and gut microbial communities has been linked to several diseases. We sought to characterize oral-fecal microbiome community coalescence, ectopic extension of oral bacteria, clinical variables contributing to this phenomenon, and associated infectious consequences by analyzing the 16S rRNA V4 sequences of longitudinal fecal (n=551) and oral (n=737) samples from 97 patients with acute myeloid leukemia (AML) receiving induction chemotherapy (IC). Clustering observed in permutation based multivariate analysis of variance (PERMANOVA) of Bray-Curtis dissimilarity and PCoA plot of UniFrac distances between intra-patient longitudinal oral-stool sample pairs suggested potential oral-stool microbial community coalescence. Bray-Curtis dissimilarities and UniFrac distances were used to create an objective definition of microbial community coalescence. We determined that only 23 of the 92 patients exhibited oral-stool community coalescence. This was validated through a linear mixed model which determined that patients who experienced coalescence had an increased proportion of shared to unique OTUs between their oral-stool sample pairs over time compared to non-coalesced patients. Evaluation of longitudinal microbial characteristics revealed that patients who experienced coalescence had increased stool abundance of Streptococcus and Stenotrophomonas compared to non-coalesced patients. When treated as a time-varying covariate, each additional day of linezolid (HR 1.15, 95% CI 1.06 – 1.24, P <0.001), meropenem (HR 1.13, 95% CI 1.05 – 1.21, P = 0.001), metronidazole (HR 1.13, 95% CI 1.05 – 1.21, P = 0.001), and cefepime (HR 1.10, 95% CI 1.01 – 1.18, P = 0.021) increased the hazard of oral-stool microbial community coalescence. Levofloxacin receipt was associated with a lower risk of microbiome community coalescence (HR 0.75, 95% CI 0.61 – 0.93, P = 0.009). By the time of neutrophil recovery, the relative abundance of Bacteroidia (P<0.001), Fusobacteria (P=0.012), and Clostridia (P=0.013) in the stool were significantly lower in patients with oral-gut community coalescence. Exhibiting oral-stool community coalescence was associated with the occurrence of infections prior to neutrophil recovery (P=0.002), as well as infections during the 90 days post neutrophil recovery (P=0.027). This work elucidates specific antimicrobial effects on microbial ecology and furthers the understanding of oral/intestinal microbial biogeography and its implications for adverse clinical outcomes.